Wacana Demokrasi dalam Pemikiran Politik Islam - Muhammad Hasbi (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2011)
This article talks about democracy concept and it relationship to religion which is concept and a means value system is extremely important in the human life. The problem is between Islam as the conviction based on divine revelation and democracy that is product of human reason as social creature. Side long, Islam actually is the initiator in political system application that very appreciate humanity and on the other side democracy system appreciated as the most appreciating system about humanity, so that almost entire government in the world include most of Islamic state accept this system. This democracy system is still in process and its fluency dependent on three component within the state, they are political will from the state, strong commitment from the political society, and strong guidance from civil society to bring the democracy system into reality. For the Muslim, this socialization will be more effective when it also done through religion approach, by the translation of that democracy ideas into religiouslanguage, and integration between it and learning of Islamic religious discipline that discuss about constitutional.